(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluating human resource management results, the cohesion of medical staff at Nguyen Tri Phuong hospital and some influencing factors. Research subjects and methods: Descriptive cross-sectional, 386 medical human at Nguyen Tri Phuong hospital. Research results: The engagement of health workers reached 81.6%. The factors of human resource allocation, working environment, training, human resource development, right to participate in the decision-making process and information transparency have good rates: 75,7%; 82,1%; 79%; 80,3% and 83,7%, respectively. The factors of human resource management all affect the engagement of health workers with p<0,05. Conclusion: Hospital leaders need to develop plans to improve the cohesion of health workers to perform well in human resource management at the hospital.